Investigating the Determinants of Health Services Utilization Among Older Adults in the Integrated Medical and Nursing Institutions in Guangxi, China - Zhu, Xiaoyu; Jittrabiab, Siriluck; Imsomboon, Thanawat; Wang, Biyan (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Guangxi, located in the less economically developed western region of China, faces an increasingly severe challenge of population aging. This study aims to explore the factors influencing the health services utilization among older adults in Guangxi’s integrated medical and nursing institution (IMNI), providing empirical evidence to enhance health services utilization among older adults and improve the integrated medical and elderly care service system. Materials and Methods: Representative IMNIs were selected from Nanning, Guilin, and Yulin, totaling 10 institutions. The study population consisted of 395 older adults aged 60 and above residing in the IMNI. The questionnaire was self-designed and underwent two rounds of expert consultation. Statistical analyses included χ2 tests, rank-sum tests, and negative binomial regression (NB). Results: Univariate analysis showed statistically significant differences between outpatient services utilization and hereditary diseases, familial frequently-occurring disease, pain, falls, times of health check-ups, SRH, changes in health assessments by institutional doctors, and satisfaction with institutional medical services (p < 0.05). Inpatient services utilization was a statistically significant difference with gender, educational level, medical insurance, hereditary diseases, chronic diseases, pain, falls, times of health check-ups, ADL, changes in health assessments by institutional doctors, and willingness to stay in the institution (p < 0.05). NB presented statistically significant differences between outpatient services utilization and pain, SRH, and changes in health assessments by institutional doctors. Inpatient services utilization was statistically significantly different by gender, educational level, pain, falls, and the frequency of health check-ups. Conclusion: Older adults in the IMNI can not only receive elderly care but also conveniently access medical services, ensuring healthy aging. However, Guangxi’s IMNI should further optimize internal medical resource allocation, enhance the quality of medical services, and explore broader collaboration with external medical resources to establish a more efficient health services network that better meets the health needs of older adults.